Greater Home Coming Ahead for Kerala - P, Mansoor (IJRDO - Journal of Social Science and Humanities Research, 2017)
The Saudi Arabian Government has introduced and implemented a series of labour policy changes recently with a view to provide more employment opportunities to the youths of the nations and hence to put an end to the persistent unemployment issues which will bring a far reaching consequences upon many countries of the world including India. The article try to address these policy changes and what can be the effect of these policies upon Kerala economy. As Indians occupies top position in the Saudi labour market, the policy changes will be crucial to India. The Keralites are very familiar with the Gulf labour market since 1970s and hence developed the renowned Kerala model of development. The contribution of Keralites in Gulf countries to the development ofstate has been increasing over the years. The new labour policy changes of Saudi Government will be causing a mass quitting of job by Keralites and this will result a very crucial changes upon the Kerala economy.